1995
DOI: 10.1159/000109437
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intracellular pH in the Control of Adenosine Output from Red Skeletal Muscle

Abstract: More than 30 years ago, it was proposed that adenosine was released from skeletal muscle in response to a decrease in the oxygen supply-to-demand ratio. It has subsequently been confirmed that adenosine is released from red muscles in proportion to the contraction frequency, but the mechanism that controls its release remains controversial. There is no direct evidence for the involvement of oxygen insufficiency in the process, and there is some indirect evidence that it is not involved. On the other hand, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…These findings suggest that in human skeletal muscle, adenosine plays a very important role in the regulation of local blood flow. Similar findings have been reported for rodent muscle 11 and canine muscle 9 ; it should be noted, however, that the level of hypoxia used in the present study is mild compared with those used in various animal models. It has been suggested, in animal preparations, that other compounds interact with adenosine to mediate the vasodilation associated with hypoxia.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…These findings suggest that in human skeletal muscle, adenosine plays a very important role in the regulation of local blood flow. Similar findings have been reported for rodent muscle 11 and canine muscle 9 ; it should be noted, however, that the level of hypoxia used in the present study is mild compared with those used in various animal models. It has been suggested, in animal preparations, that other compounds interact with adenosine to mediate the vasodilation associated with hypoxia.…”
supporting
confidence: 89%
“…However, it has been shown that during systemic hypoxia, the release of adenosine from canine skeletal muscle was increased. 9 Furthermore, it has been demonstrated in rodent muscle that adenosine largely mediates the vasodilation associated with systemic hypoxia 10,11 and that this vasodilation was dependent on nitric oxide synthesis. 10 However, whether these same substances or mechanisms are responsible for the hypoxia-induced vasodilatation in human skeletal muscle is unclear.…”
mentioning
confidence: 99%
“…However, studies using experimental models other than the perfused rat hindquarter have clearly demonstrated that adenosine production is markedly enhanced during both muscle contractions (Tomaniga et al 1980; Ballard et al 1987; Achike & Ballard, 1993) and hypoxia (Marshall et al 1993; Skinner & Marshall, 1996). In fact, it has been shown that muscle adenosine release is closely correlated with venous lactate concentration and pH (Ballard, 1995; Mo & Ballard, 1997). In the current experiments, venous lactate concentration was markedly elevated during both contractions and hypoxia, whereas venous pH was significantly depressed only during hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated extracellular adenosine is detectable in cultures of primary rat skeletal muscle fibers activated by electrical stimulation(361, 362, 562). Lactic acid and low intracellular pH both are associated with elevated release of adenosine from skeletal muscle cells (50, 51). Endothelial cells also release adenosine (207, 208).…”
Section: Training Adaptations Within the Active Muscle: Increased mentioning
confidence: 99%